The role of education in economic growtht: theory, history, and current returns. (2012)
Evidence is presented that economic development requires both human capital and physical capital and that historically human capital has been the limiting factor in national development. Education has direct and indirect effects on national income. Evidence is presented that the indirect effects are very large and larger than the direct effects in poor countries. The indirect effects are not very large and are smaller than the direct effects in rich countries. Investment in education has diminishing returns. Macro returns exceed 50 percent in poorly-educated countries and 12 percent in highly-educated countries.